Efektifitas Pelaksanaan Sertifikasi Tanah Wakaf Di Kecamatan Mojoroto Kota Kediri - Muhammad Saiful Bahri; Abbas Sofwan Matlail Fajar (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The obligation to submit an application for a waqf land certificate is regulated in Government Regulation Number 25 of 2018 Article 51 A Paragraph (1) that